Implementing an encrypted display with the electron-induced colour router array - Hyoseok Park; Minsu Park; Yeonsang Park (Light: Science & Applications)
Abstract Electron-induced colour routers actively manipulate dichromatic photon momentum at deep subwavelength scales, enabling programmable encrypted displays with enhanced security and high integration for advanced photonic applications.